Emprego e trabalho no início do século XXI: Revisitando keynes e marx - de Moraes Neto, Benedito Rodrigues [UNESP] (My University, 2014)
The nature of labor in advanced economies has presented a significant change lately. The technological process has resulted in the reduction of labor without content and the expansion of labor with higher qualification or schooling, a phenomenon that can be discussed by turning to Keynes and Marx. As far as Keynes is concerned, his foresight was that technological progress would generate a huge reduction of labor time and the expansion of leisure time. Since this did not occur, the failure may be attributed to the fact of having worked with opposition between labor without content and leisure. Thus, it was not possible to capture the historical changes in labor and man’s relationship with it. Marx’s viewpoint is completely different, because his opposition takes place between labor without content and activity labor, the latter impregnated with content and essential to the development of individualities. Therefore, present reality has a greater identification with Marx and presents major challenges to capitalism and its critique.
Employment and labor in early twenty-first century: Revisiting keynes and marx
Keywords: Employment; Keynes; Labor; Marx; Technical progress